Susceptibility to 18 drugs and multidrug resistance of Arcobacter isolates from different sources within the Czech Republic - Šilha, David; Pejchalová, Marcela; Šilhová, Lucie (Journal of global antimicrobial resistance, 2017)
OBJECTIVES: Arcobacter spp. are considered to be potential foodborne pathogens, and consumption of contaminated food containing these bacteria could endanger human and animal health. Arcobacter butzleri and Arcobacter cryaerophilus are the species most frequently isolated from food of animal origin and from other samples. The aim of this study was to evaluate the susceptibility of arcobacters isolated in the Czech Republic. No information about antibiotic susceptibility and multidrug resistance of arcobacters isolated in the Czech Republic is available in the literature before now. METHODS: The antimicrobial resistance of A. butzleri (n=80) and A. cryaerophilus (n=20) isolated from meat of animal origin, water sources and clinical samples was examined by the disk diffusion method. RESULTS: Arcobacters were resistant to one or more antimicrobial agents in 99% (99/100) of tested isolates. Most of the Arcobacter isolates were resistant to β-lactam antibiotics, i.e. ampicillin (81.0%), amoxicillin/clavulanic acid (28.0%), cefalotin (73.0%) and aztreonam (93.0%). Arcobacters were also frequently resistant to lincosamides, i.e. clindamycin (98.0%). Of the aminoglycosides, amikacin, gentamicin and tobramycin were evaluated to be the most effective antibiotics among those tested against arcobacters. CONCLUSIONS: These results demonstrate substantial resistance in Arcobacter isolates to 18 antimicrobial agents commonly used in medical and veterinary medicine. Multidrug resistance was found in 93.8% (75/80) of A. butzleri isolates and 70.0% (14/20) of A. cryaerophilus isolates.
Keywords: Food Microbiology; Antibiotic; Gram-Negative Bacterial Infections; Arcobacter; Antimicrobial susceptibility testing; lidé; Arcobacter spp.; gramnegativní bakteriální infekce; Anti-Bacterial Agents; potravinářská mikrobiologie; Susceptibility; Czech Republic; Antibiogram; mnohočetná bakteriální léková rezistence; diskové difúzní antimikrobiální testy; Česká republika; Drug Resistance, Multiple, Bacterial; Water Microbiology; mikrobiologie vody; antibakteriální látky; Disk Diffusion Antimicrobial Tests; Humans